Rule-based vs. intuition-based generative design: an inquiry into the digital chain concept in undergraduate architectural education. (18th December 2017) - Abdelmohsen, Sherif; Massoud, Passaint; Tarabishy, Sherif; Hassab, Ahmed
Abstract: While the digital chain concept has been explored in a number of architectural projects, only a few have pedagogically investigated the specific generative design methods in such a process. Different schools of thought have emerged in this regard. Some promote the rule-based approach, where specific rules are more dominant than inspiration and intuition, and vice versa. Based on an inquiry into the digital chain concept within the context of a digital design course, we argue that there exists a set of dynamics that govern the implemented generative methods, that is neither fully rule-based nor intuition-based, but a hybrid of both. Abstract : Revisiting the digital chain based on a hybrid intuition-based/rule-based process: (a) concept generation based on intuition and inspirations, (b) back and forth digital experimentation and material exploration, (c) informed rule-based and algorithmic translation based on feedback from conceptual departure, intuition, and digital experimentation, (d) parametric modeling process, (e) preparation for fabrication based on material exploration and parametric modeling